Nonsense Verse - Lewis Carroll & R.B. Murphy
Why not walk with the Walrus and the Carpenter, whiffle through the tulgey wood with the Jabberwocky, and join the whiting's dance in this delightful collection of some of Lewis Carroll's best-loved nonsense poems and limericks?